Nursing theories conceptual & philosophical foundations - Kim, Hesook Suzie; Kollak, Ingrid (Springer Pub. Co, 2006)
"This book is written for advanced nursing students. The second edition of Nursing theories explores the conceptual and philosophical foundations of selected major nursing theories. The book is not a survey or evaluation of nursing theories, but is designed to assist students in understanding the core philosophical concepts behind nursing theories and how they can be applied to current nursing practice. New to this second edition: Essays warranted by developments in the science and research of nursing. Three chapters addressing: pragmatism, evidence-based nursing, biography. Newly authored chapters on systems and transcultural thoughts reflecting current thinking and new directions. Completely rewritten chapters on interaction and self-care to incorporate current debates"--Provided by the publisher.